2020
DOI: 10.5539/jel.v10n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the Importance of Maintaining Internship Support for College Student Engagement and Anticipated Employment

Abstract: The Covid-19 pandemic has created many challenges for universities around the world, including how to keep students engaged in their professional development, despite the challenges of remote learning and virtual student services. The goal of this study was to demonstrate the continued importance of Career Professional Development Center (CPDC) support (pre-pandemic to early stages of the pandemic) for business-related internships influencing student professional development engagement (PDE) and anticipated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Although acknowledged to be important to maintain as a college student resource during the COVID-19 pandemic (Russell et al, 2021), no prior empirical work has been done testing Academic Advising. In addition, this study expands the scope of prior empirical work of Blau et al (2021), who demonstrated the importance of internship support to business students during the early pandemic period. There was weak support for the first research question, only Attendance Motivation changed significantly from 2019 to 2020 and it understandably decreased as students were suddenly forced to leave the main campus and all face-to-face classes were cancelled on March 13, 2020, approximately half-way through the Spring, 2020 semester.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Although acknowledged to be important to maintain as a college student resource during the COVID-19 pandemic (Russell et al, 2021), no prior empirical work has been done testing Academic Advising. In addition, this study expands the scope of prior empirical work of Blau et al (2021), who demonstrated the importance of internship support to business students during the early pandemic period. There was weak support for the first research question, only Attendance Motivation changed significantly from 2019 to 2020 and it understandably decreased as students were suddenly forced to leave the main campus and all face-to-face classes were cancelled on March 13, 2020, approximately half-way through the Spring, 2020 semester.…”
Section: Discussionmentioning
confidence: 54%
“…Such resources are important for college student retention and graduation (Swecker, Fifolt & Searby, 2013). With the exception of Blau, Snell and Goldberg (2021) the authors found an absence of specific empirical research and only general recommendations on the need to consider these two non-teaching student resources as a University responded to COVID-19 challenges (Russell et al, 2021). Using two independent graduating business undergraduate samples, across pre and early pandemic periods, Blau et al (2021) empirically demonstrated the importance of students having at least one internship experience (versus none) for a higher anticipation level by graduation to have subsequent full-time employment.…”
Section: Relevant Scholarshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Internships have long been noted to be an important gateway to full-time job employment for college students (Knouse & Fontenot, 2008;Sagen, Dallam & Laverty, 2000). Blau, Snell and Goldberg (2021) found that college business students with at least one internship, versus those with no internships, were more likely to anticipate both outcomes of full-time employment by graduation and full-time employment within their major by graduation. Prior research has shown a distinction between these two outcomes, i.e., that a higher percentage of graduating business students anticipate full-time employment versus full-time employment in their major (Blau, Gaffney, Kim & Jarrell, 2017).…”
Section: Relevant Prior Scholarshipmentioning
confidence: 93%